THE ROLE OF SATISFACTION IN MEDIATING THE EFFECT OF SERVICE QUALITY ON COFFEE FARMERS’ LOYALTY AS PARTNER FARMERS OF PUNTANG COFFEE SME, BANDUNG REGENCY - Narsiska Darmawan; Effy Yuswita; Neza Fadia Rayesa (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2026)
Puntang Coffee is one of Small Medium Enterprises (SMEs) in the coffee processing industry that provides various types of green coffee beans and roasted beans in West Java. It is known that there is an increase in new customers from Puntang Coffee by 10% per year with an average demand for coffee shops and roastery for green beans products of at least 50 - 100 kg. However, this was not accompanied by the growth of partner farmers, which actually tended to decrease during 2022- 2023, namely by 7.6% and 3.7%. The decrease in the number of partner members can indicate that there are problems regarding the loyalty of partner farmers of Puntang Coffee. Therefore, this study aimed to identify the effect of service quality on the loyalty of Puntang Coffee partner farmers with satisfaction as a mediating variable. This study used a quantitative approach with accidental sampling as the sampling technique to collected data from 84 respondent. The analysis used is SEM-PLS with SmartPLS 4.0. The results shown that the service quality variable has a positive and significant effect on the partner farmers’ loyalty variable, the service quality variable has a positive and significant effect on the partner farmers’ satisfaction variable, the member satisfaction variable has a positive and significant effect on partner farmers’ loyalty, and the service quality variable has a positive and significant effect on the partner farmers’ loyalty variable through satisfaction as a mediating variable.